2020
DOI: 10.1021/acsinfecdis.0c00523
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationship of Dehydrodieugenol B Neolignans against Trypanosoma cruzi

Abstract: Trypanosoma cruzi is the etiologic agent of Chagas disease, which affects over seven million people, especially in developing countries. Undesirable side effects are frequently associated with current therapies, which are typically ineffective in the treatment of all stages of the disease. Here, we report the first synthesis of the neolignan dehydrodieugenol B, a natural product recently shown to exhibit activity against T. cruzi. Using this strategy, a series of synthetic analogues were prepared to explore st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…CoMFA and CoMSIA techniques employ probe atoms (in general, a positively charged sp 3 carbon) to obtain molecular interaction fields and a range of different similarity indices, respectively, that are related to the biological data [ 26 , 39 ]. To construct CoMFA and CoMSIA models, we used the molecular alignment based on the technique known as maximum common substructure (MCS) of the training molecules (grid spacing = 2 Å, and energy cut-off = 30 kcal/mol) [ 26 , 39 ]. To construct the CoMFA models, we calculated molecular interaction (steric and electrostatic) fields by using a probe atom from the Lennard–Jones and Coulomb potentials, respectively [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…CoMFA and CoMSIA techniques employ probe atoms (in general, a positively charged sp 3 carbon) to obtain molecular interaction fields and a range of different similarity indices, respectively, that are related to the biological data [ 26 , 39 ]. To construct CoMFA and CoMSIA models, we used the molecular alignment based on the technique known as maximum common substructure (MCS) of the training molecules (grid spacing = 2 Å, and energy cut-off = 30 kcal/mol) [ 26 , 39 ]. To construct the CoMFA models, we calculated molecular interaction (steric and electrostatic) fields by using a probe atom from the Lennard–Jones and Coulomb potentials, respectively [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…To construct CoMFA and CoMSIA models, we used the molecular alignment based on the technique known as maximum common substructure (MCS) of the training molecules (grid spacing = 2 Å, and energy cut-off = 30 kcal/mol) [ 26 , 39 ]. To construct the CoMFA models, we calculated molecular interaction (steric and electrostatic) fields by using a probe atom from the Lennard–Jones and Coulomb potentials, respectively [ 26 ]. Regarding the CoMSIA models, different similarity indices (steric, electrostatic, hydrophobic, H-bond donor, and H-bond acceptor) were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 As neolignans are a diverse group of chemical structures present in several plant families and responsible for multiple biological activities, we chose to investigate the trypanomicidal potential of a set of neolignans. [8][9][10][11] Some studies [12][13][14] have reported the importance of neolignans as promising compounds in the treatment against T. cruzi.…”
Section: Introductionmentioning
confidence: 99%